31 hope that helps have a good one
Step-by-step explanation:
6x - 3x^2 + 2x^2 -2x = 5x^2 + 15x
4x -x^2 = 5x^2 + 15x
-11x - 6x^2 = 0
-6x^2 - 11x = 0
use the quadratic formula
(-b±√(b²-4ac))/(2a)
Answer:
c.
$23,271
Step-by-step explanation:
i took the same test on edg
Answer:
h= -8/3
Picture Explanation:
- Divide 3 on both sides of the equal sign, as shown above, so (h) can be alone.
- Since negative 8, let alone positive 8, can't be divided into 3, you simply leave the fraction as is. So you're left with (h= -8/3)
<em><u>Hope this makes sense.</u></em>